Population-based screening for colorectal cancer in Wuhan, China - Liu, Song; Wang, Yifan; Wang, Yuying; Duan, Chaofan; Liu, Fan; Zhang, Heng; Tian, Xia; Ding, Xiangwu; Zhang, Manling; Cao, Dan; Liu, Yi; Jiang, Ruijingfang; et al. (Frontiers in Oncology, 2024)
Fecal DNA test has emerged as a non-invasive alternative for colorectal cancer (CRC) screening in average-risk population. However, there is currently insufficient evidence in China to demonstrate the effectiveness of population-based CRC screening using fecal DNA based test. Here, a large-scale real-world study for CRC screening was implemented in Wuhan, Hubei province, China. A total of 98,683 subjects aged between 45 and 60 years were screened by a fecal DNA test (ColoTect®) which detected methylation status of SDC2, ADHFE1, and PPP2R5C. Participants who tested positive were advised to receive diagnostic colonoscopy. 4449 (4.5%) subjects tested positive for fecal DNA test, and 3200 (71.9%) underwent colonoscopy. Among these, 2347 (73.3%) had abnormal colonoscopy findings, of which 1330 (56.7%) subjects received pathological diagnosis. Detection rates for CRC and advanced precancerous lesions were 1.3% and 2.3%, respectively. Detection rates for nonadvanced adenomas and polyps were 14.0% and 21.6%, respectively. 28.0% of all colonoscopies showed colorectal neoplasm but lack pathological diagnosis. 6.1% showed other abnormalities such as enteritis. In conclusion, preliminary real-world evidence suggested that fecal DNA tests had promising diagnostic yield in population-based CRC screening. Clinical Trial Registration: [https://www.chictr.org.cn/showproj.html?proj=192838], identifier [ChiCTR2300070520].